Prepartal infection of the placenta with Neisseria gonorrhoeae. Issue 2 (April 1985) - Yvert, F; Frost, E; Walter, P; Gass, R; Ivanoff, B
Abstract : Placentas from 191 consecutive deliveries were cultured for Neisseria gonorrhoeae and other bacteria before being examined histologically. N gonorrhoeae was seen on direct microscopical examination and cultured from two placentas, one of which had chorioamnionitis and the other had a granulocytic invasion of the membranes. In both patients, rupture of the membranes had occurred two hours or less before delivery, and thus after infection. A third patient was also found to have light gonococcal infection of the placenta. Six infections with group B streptococci were identified, but only one correlated with chorioamnionitis. Chorioamnionitis was observed in 16 (8.4%) and granulocytic infiltration of the membranes in 18 (9.4%) of the deliveries.